Cypherpunk - André Ramiro; Ruy de Queiroz (Internet Policy Review)
Cypherpunk refers to social movements, individuals, institutions, technologies, and political actions that, with a decentralised approach, defend, support, offer, code, or rely on strong encryption systems in order to re-shape social, political, or economic asymmetries. Based on a literature review that encompassed the last thirty years, bringing together iconic manifestos, seminal works on Internet social movements, as well as contemporary academic research developments, the entry offers a sedimentation of the significance of cypherpunk phenomena. It argues that “cypherpunk” constitutes a socio technical expression of the promotion of rights through cryptography, meaning that it can be considered to have a broader area of incidence. Therefore, going further in order to give elasticity to the term, the entry covers not only the diversity of political rationale behind the development, promotion and reliance on encryption, but also to classify the variety of expressions of cypherpunk beyond individuals and collectives, but also organisations and technologies that constitute contemporary networks of political participation.